2015
DOI: 10.1002/alr.21639
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal fibrosarcoma: analysis of the Surveillance, Epidemiology, and End Results database

Abstract: SNFS is a rare entity. This study represents the largest series of SNFS to date. The mainstay of treatment for this tumor is surgical resection with or without radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 31 publications
1
22
2
2
Order By: Relevance
“…In the current study, we identified 237 cases of malignant fibrous neoplasms of long bone based on the SEER database from 1973 to 2015. The OS and CSS rates at 5 years were 39.7 and 60.3%, respectively, while the previous study results showed that the OS and CSS of sinonasal fibrosarcoma were 71.7 and 77.8%, respectively [13].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In the current study, we identified 237 cases of malignant fibrous neoplasms of long bone based on the SEER database from 1973 to 2015. The OS and CSS rates at 5 years were 39.7 and 60.3%, respectively, while the previous study results showed that the OS and CSS of sinonasal fibrosarcoma were 71.7 and 77.8%, respectively [13].…”
Section: Discussioncontrasting
confidence: 57%
“…These tumours can infiltrate adjacent tissues and metastasize distally [13][14][15][16][17][18][19]. However, the outcome and prognosis of patients with MFN of long bones have not been reported because of its rarity.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The paranasal sinus is one of the rarest locations for fibrosarcoma, with only a few cases having been reported in the literature since the year 2000, [1][2][3][4][5][6] although there have been comprehensive reviews on the treatment results and demographic and clinicopathological features of paranasal sinus fibrosarcoma. 7,8 The tissue origin of paranasal sinus fibrosarcoma seems to be the periosteum rather than mucosal connective tissue. 9 Paranasal sinus fibrosarcoma is commonly seen in middle-aged patients, with both genders being equally affected.…”
Section: Introductionmentioning
confidence: 99%
“…9 Paranasal sinus fibrosarcoma is commonly seen in middle-aged patients, with both genders being equally affected. 7 It can be further divided into infantile type and adult type, 4,10 and in routine clinical practice, adult-type sinonasal fibrosarcoma is easy to misdiagnose as other neoplasms because of its rarity and non-specific symptomatology. 2,7 Additionally, although basic information on this disease has been reported, there are only limited studies examining the imaging characteristics of paranasal sinus fibrosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Sinonasal teratocarcinosarcoma is an extremely rare and highly aggressive malignant neoplasm, with complex components of mesenchymal, epithelial, and neuroectodermal elements; it is not easy to forecast its trend of development and prognosis owing to its uncertain clinical behavior [ 6 ]. Other histological tumor types reported in the sinonasal tract include Ewing’s sarcoma/PNET, malignant fibrous histiocytoma, chondrosarcoma and osteosarcoma, fibrosarcomas, leiomyosarcomas, and synovial sarcoma [ 7 11 ].…”
Section: Introductionmentioning
confidence: 99%